Interfacial Defects Change the Correlation between Photoluminescence, Ideality Factor, and Open‐Circuit Voltage in Perovskite Solar Cells. Issue 33 (6th July 2021) - Kim, Sohyeon; Jang, Jun Hyeok; Wu, Ziang; Lee, Mi Jung; Woo, Han Young; Hwang, Inchan
Abstract: The ideality factor ( n id ) and photoluminescence (PL) analyses assess charge recombination characteristics in perovskite solar cells (PeSCs). However, their correlations with open‐circuit voltage ( V oc ) are often found to be complicated depending on the recombination types in the devices. Herein, the correlation of n id, PL characteristics and V oc is elucidated depending on the interfacial crystal quality in triple‐cation mixed‐halide perovskite, Cs0.05 (MA0.17 FA0.83 )0.95 Pb(I0.83 Br0.17 )3, deposited on different hole transport layers (HTLs). In the devices with low quality interfacial crystals, V oc increases together with n id, which originates from the light intensity‐dependence of majority carrier at the interface. Meanwhile, a negative correlation between V oc and n id is observed for devices with high quality interfacial crystals. The authors discuss the cases that PL enhancement by the improvement of overall crystal quality can fail to correlate with a V oc increase if interfacial crystal quality becomes worse. The study highlights that interfacial crystal quality evaluation can help to understand charge recombination via n id and PL measurements, and more importantly provide information of which defect engineering between at the interface and in the bulk would be more effective for device optimization. Abstract : Quantitative evaluation of interfacial crystals qualities in perovskite solar cells helps the understanding of charge recombination and their effects on the relationship between the ideality factor/photoluminescence and open‐circuit voltage. Furthermore, this simple strategy provides the information of which defect engineering will be more effective in solar cells.